Decreased postural control in adult survivors of childhood cancer treated with chemotherapy - Einarsson, Einar-Jón (Sci Rep, 2016)
The objective of cancer treatment is to secure survival. However, as chemotherapeutic agents can affect the central and peripheral nervous systems, patients must undergo a process of central compensation. We explored the effectiveness of this compensation process by measuring postural behaviour in adult survivors of childhood cancer treated with chemotherapy (CTS). We recruited sixteen adults treated with chemotherapy in childhood for malignant solid (non-CNS) tumours and 25 healthy age-matched controls. Subjects performed posturography with eyes open and closed during quiet and perturbed standing. Repeated balance perturbations through calf vibrations were used to study postural adaptation. Subjects were stratified into two groups (treatment before or from 12 years of age) to determine age at treatment effects. Both quiet (p = 0.040) and perturbed standing (p ≤ 0.009) were significantly poorer in CTS compared to controls, particularly with eyes open and among those treated younger. Moreover, CTS had reduced levels of adaptation compared to controls, both with eyes closed and open. Hence, adults treated with chemotherapy for childhood cancer may suffer late effects of poorer postural control manifested as reduced contribution of vision and as reduced adaptation skills. These findings advocate development of chemotherapeutic agents that cause fewer long-term side effects when used for treating children.